The stories Julian tells - Cameron, Ann, 1943-; Strugnell, Ann. (New York : Pantheon Books, 1981)
Relates episodes in seven-year-old Julian's life which include getting into trouble with his younger brother Huey, planting a garden, what he did to try to grow taller, losing a tooth, and finding a new friend.
520
Keywords: Family life -- Fiction; Friendship -- Fiction; African Americans -- Fiction